2018
DOI: 10.1002/lary.27165
|View full text |Cite
|
Sign up to set email alerts
|

Clinical relevance of endoscopic three‐dimensional imaging for quantitative assessment of phonation

Abstract: 4. Laryngoscope, 128:2367-2374, 2018.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
15
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 17 publications
(28 citation statements)
references
References 45 publications
(102 reference statements)
1
15
0
1
Order By: Relevance
“…The measured amplitudes and velocities may be compared with those obtained for human vocal folds in in vivo (∼1-2 mm and ∼2 m/sec, respectively) [31] and excised (∼2 mm and ∼1 m/s, respectively) [29]. However, the human excised larynx exhibited an induced reduced amplitude, presumably significantly affecting the normal kinematics of the contralateral vocal fold that, while mechanically normal, came into contact with a vocal fold of atypical stiffness.…”
Section: Stroboscopic Oct-vs Modementioning
confidence: 98%
See 1 more Smart Citation
“…The measured amplitudes and velocities may be compared with those obtained for human vocal folds in in vivo (∼1-2 mm and ∼2 m/sec, respectively) [31] and excised (∼2 mm and ∼1 m/s, respectively) [29]. However, the human excised larynx exhibited an induced reduced amplitude, presumably significantly affecting the normal kinematics of the contralateral vocal fold that, while mechanically normal, came into contact with a vocal fold of atypical stiffness.…”
Section: Stroboscopic Oct-vs Modementioning
confidence: 98%
“…Ultrasound imaging has been used to trace tissue particles in motion pictures along the coronal plane with good penetration, but it suffered from poor spatial resolution [26,27]. Optical imaging based on structured illumination has been used to measure vocal fold kinematics in both excised and in vivo experimental configurations [28][29][30][31]. Whereas this method allowed for fast imaging rates (∼4000 fps), it suffered from poor spatial resolution (10 points per line) and significant computational overhead for vocal fold surface reconstruction.…”
Section: Introductionmentioning
confidence: 99%
“…Recently, laryngeal image processing of vocal folds motion have been used to visualize the 3D superior vocal fold vibrations from laryngeal recordings [23,24,[167][168][169]. The authors proved that healthy phonation does not depend on symmetric oscillation patterns since great asymmetric vertical dynamics were observed.…”
Section: Voice Research and Clinical Applicationsmentioning
confidence: 99%
“…Current laryngeal image modalities include Laryngeal VS, Videokymography (VKG), High-Speed Digital Kymograghy (DKG) and Laryngeal HSV. However, there are new modalities that emerge for analyzing the vocal folds dynamics [22] and also devices for 3D visualization of the vibration of vocal folds superior margins [23][24][25][26]. This paper is focused on two laryngeal image modalities: VS and HSV.…”
Section: Laryngeal Image Modalitiesmentioning
confidence: 99%
“…They oscillate self-sustained with a high frequency and small amplitude. A study on ten individuals showed that the average fundamental frequency for males is around 174 Hz and for females around 278 Hz, and the lateral amplitudes are around 0.93 mm and 0.80 mm [19].…”
Section: Anatomical Structure Of the Vocal Foldsmentioning
confidence: 99%